Application of caged compound in selective removal of ethanol and application of caged compound
Through the multi-channel adsorption characteristics of cage-shaped compound solid powder materials, the problem of removing ethanol impurities in vinyl acetate is solved, and an efficient and low-energy-consuming separation process is achieved, production costs are reduced, and the stability and reusability of the material are ensured.
Patent Information
- Application Number
- CN202311356846.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-12
- Filing Date
- 2023-10-19
- Publication Date
- 2025-01-14
AI Technical Summary
The prior art is difficult to efficiently remove ethanol impurities in vinyl acetate, resulting in complex separation process, high energy consumption, large investment, and failure to effectively solve the problem of ethanol removal in vinyl acetate.
The cage-like compound solid powder material is used to absorb ethanol in vinyl acetate through the cavity, port and outer wall of its structure through multiple channels to selectively remove impurities ethanol, and the material can be reused to reduce energy consumption and production costs.
It realizes efficient removal of ethanol in vinyl acetate, the separation process is simple, the equipment requirements are low, no distillation operation is required, low energy consumption, high material stability, reduced cost, excellent adsorption efficiency, and can be recycled.
Smart Images

Figure CN119306602A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical engineering, and in particular to a method for removing impurity ethanol from vinyl acetate. Background Art
[0002] Vinyl acetate (VAc) is a colorless, transparent liquid with a strong odor. It is one of the 50 largest chemical raw materials in the world. As an important organic chemical raw material, it is mainly used to produce derivatives such as polyvinyl acetate (PVAc), polyvinyl alcohol (PVA), ethylene-vinyl acetate copolymer (EVA), vinyl chloride-vinyl acetate copolymer (EVC), and polyacrylonitrile comonomer. These derivatives are widely used in chemical products such as coatings, slurries, adhesives, vinylon, films, vinyl copolymer resins, and acetal resins. Therefore, the purity of vinyl acetate directly affects the quality of these derivatives. Vinyl acetate produced from the existing synthesis process contains unreacted raw materials and by-products, so vinyl acetate needs to be further purified.
[0003] Ethanol impurities are usually present in vinyl acetate. Ethanol is an organic compound with the molecular formula C2H6O, commonly known as alcohol. Ethanol has a very wide range of uses in the chemical industry. It can be used to produce chemical raw materials such as acetaldehyde, acetic acid, ether, ethyl acetate, ethylamine, etc. It is also a raw material for producing solvents, dyes, coatings, flavors, pesticides, medicines, rubber, plastics, artificial fibers, detergents and other products. At present, the separation method for vinyl acetate and ethanol is the separation technology of vinyl acetate device via gas phase oxidation. However, when vinyl acetate and ethanol impurities are present, the separation process is complicated, the investment is large, and the energy consumption is high.
[0004] Chinese patent CN115894237A discloses a method for separating and purifying vinyl acetate, using cucurbituril[6] channel-type crystal material as an adsorbent to selectively adsorb acetaldehyde in a vinyl acetate mixed solution to achieve separation and purification of vinyl acetate; the separation process of the invention is simple to operate, has low equipment requirements, and has excellent separation effect; the separation process does not require distillation operation, has low energy consumption, saves energy, and has low purification cost; the materials used are highly stable and can be regenerated and reused.
[0005] However, it does not disclose how to efficiently remove the ethanol impurity that is usually present in vinyl acetate.
[0006] The invention provides a method for removing impure ethanol from vinyl acetate, which utilizes cage-like compound solid powder material to adsorb ethanol in vinyl acetate, has low energy consumption and simple process. Summary of the invention
[0007] In view of the deficiencies in the art, the present invention provides a method for removing impure ethanol from vinyl acetate, which utilizes cage-like compound solid powder materials to adsorb ethanol in vinyl acetate, with low energy consumption and simple process.
[0008] The present invention provides a use of a caged compound for selectively removing ethanol impurities, wherein the caged compound has the structural formula
[0009]
[0010] Labeled as Q[n], where: n is any integer selected from 5-8.
[0011] Preferably, the present invention provides the use of a caged compound for selectively removing ethanol, wherein the caged compound is a solid powder.
[0012] When n=5, the outer diameter of the solid powder Q[5] is The cavity diameter is Port diameter is
[0013] When n=6, the outer diameter of the solid powder Q[6] is The cavity diameter is
[0014] Port diameter is
[0015] When n=7, the outer diameter of the solid powder Q[7] is The cavity diameter is
[0016] Port diameter is
[0017] When n=8, the outer diameter of the solid powder Q[8] is The cavity diameter is
[0018] Port diameter is
[0019] The present invention also provides a method for removing ethanol impurities from vinyl acetate by using a caged compound to selectively remove ethanol, wherein the molar ratio of the solid powder material of the caged compound to the impurity ethanol in the vinyl acetate is (1-1.5):1.
[0020] Preferably, the present invention also provides a method for removing ethanol impurities from vinyl acetate by using a caged compound to selectively remove ethanol, wherein the solid powder of the caged compound is selected from at least one of Q[5] solid powder, Q[6] solid powder, Q[7] solid powder, and Q[8] solid powder.
[0021] Preferably, the present invention also provides a method for removing ethanol impurities from vinyl acetate by using a cage-like compound to selectively remove ethanol. After selectively adsorbing ethanol, the solid powder of the cage-like compound can be desorbed and regenerated for reuse.
[0022] Preferably, the present invention also provides a method for removing ethanol impurities from vinyl acetate by using a caged compound to selectively remove ethanol. After selectively adsorbing ethanol, the solid powder of the caged compound can be desorbed and regenerated and reused. The desorption and regeneration temperature is 100-120°C.
[0023] Preferably, the present invention also provides a method for removing ethanol impurities from vinyl acetate by using a caged compound to selectively remove ethanol, wherein the temperature for selectively removing the impurity ethanol from the vinyl acetate is ≤50°C, preferably 30-50°C.
[0024] Preferably, the present invention also provides a method for removing ethanol impurities from vinyl acetate by using a caged compound to selectively remove ethanol, wherein the vinyl acetate is a mixture of vinyl acetate containing ethanol.
[0025] Preferably, the present invention also provides a method for removing ethanol impurities from vinyl acetate by using a caged compound to selectively remove ethanol, wherein the vinyl acetate is a mixture of vinyl acetate containing ethanol, and the mixture of vinyl acetate containing ethanol can be a crude product of vinyl acetate containing impurities obtained in large-scale industrial production.
[0026] The present invention also provides the use of the cage-like compound to selectively remove ethanol, a method for removing ethanol impurities from vinyl acetate, and the use of the cage-like compound in removing impure ethanol in the industrial production of vinyl acetate.
[0027] Compared with the prior art, the present invention has the following main advantages: (1) the separation process is simple to operate and has low equipment requirements; (2) the separation process does not require distillation operation, has low energy consumption, and saves energy; (3) the present invention uses Q[n] solid powder material, which further reduces the cost compared with the crystal material used in the prior art; at the same time, the powder can adsorb ethanol through multiple channels such as the cavity, port and outer wall of its molecules, and has a better adsorption efficiency than the crystal; (4) the Q[n] solid powder material used is highly stable and can be recycled without reducing the separation effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Q[6] Material structure diagram
[0029] Figure 2 Schematic diagram of the material structure of Q[5], Q[7], and Q[8]
[0030] Figure 3 This is a GCMS characterization result diagram of vinyl acetate without impurities in Example 1;
[0031] Figure 4 This is a GCMS characterization result diagram of the adsorption of ethanol from vinyl acetate containing ethanol impurities by the Q[6] solid powder material of Example 2;
[0032] Figure 5 The Q[6] solid powder material of Example 3 after desorption 1 H NMR characterization results. DETAILED DESCRIPTION
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as commonly understood by those of ordinary skill in the art to which the invention belongs. Although any methods and materials similar or equivalent to those described herein can be used to implement or test the present invention, preferred methods and materials are described herein. For purposes of the present invention, the following terms are defined below.
[0034] Caged compounds
[0035] The caged compound of the present invention is cucurbituril (also known as cucurbituril, Cucurbit[n]urils, abbreviated as Q[n]s or CB[n]s), which is a highly symmetrical caged compound composed of 2n methylene bridged n glycoside urea units. In the caged compound of the present invention, n is any integer selected from 5-8. The overall appearance is very similar to pumpkin, and the main monomer glycoside urea is similar to gourd. Pumpkin and gourd belong to the same family Cucurbitaceae (Latin: cucurbia), and urea is used as a raw material in the synthesis process, so it is finally named cucurbituril.
[0036] When n=6 in the cage compound of the present invention, the cage compound is Q[6].
[0037] The structural data and schematic diagram of the Q[6] solid powder material of the present invention are as follows:
[0038] parameter Serial number Q[6] outer diameter a 14.4 Cavity diameter b 5.8 Port diameter c 3.9 high d 9.1 Cavity volume 164 .
[0039]
[0040] In addition, Q[6] solid powder material has some homologues, such as Q[5], Q[7], and Q[8]. Their structures and structural parameters are as follows:
[0041] parameter Serial number Q[5] Q[7] Q[8] outer diameter a 13.1 16.0 17.5 Cavity diameter b 4.4 7.3 8.8 Port diameter c 2.4 5.4 6.9 high d 9.1 9.1 9.1 Cavity volume 82 279 479
[0042] Use of caged compounds for selective removal of ethanol
[0043] The use of the caged compound for selectively removing ethanol in the present invention is to utilize the caged compound, such as Q[6] solid powder material, to selectively remove ethanol from vinyl acetate;
[0044] Due to the difference in molecular structure between ethanol and vinyl acetate, the Q[6] solid powder material in the separation method can form a host-guest complex with ethanol. The host-guest complex is unstable and will gradually decomplex when heated to above 80°C, releasing the adsorbed ethanol. After the desorption process is completed, the Q[6] solid powder material can be reused without a decrease in selectivity.
[0045] The adsorption method uses Q[6] solid powder material to selectively adsorb ethanol in vinyl acetate containing ethanol as an impurity, and after removing ethanol from vinyl acetate, the Q[6] solid powder material is air-dried at room temperature to remove the mixture adsorbed on the surface, and finally desorbed to obtain a reusable Q[6] solid powder material.
[0046] The time for air-drying the Q[6] solid powder material at room temperature to remove the mixture adsorbed on the surface can be adjusted according to the sample amount. Under the condition of less than 60°C, the host-guest complex still exists stably, and the mixture of ethanol and vinyl acetate adsorbed on the surface can be gradually removed.
[0047] The ethanol molecules adsorbed in the Q[6] solid powder material can be desorbed by heating, preferably at a temperature of 100-120°C, and the desorption time can be adjusted according to the sample amount. At this temperature, the host-guest complex is unstable, and the adsorbed ethanol molecules will gradually be released, while the Q[6] solid powder material is stable. After desorption, the Q[6] solid powder material can continue to be used to remove impurity ethanol from vinyl acetate for the next cycle.
[0048] Crude vinyl acetate containing impurities
[0049] The crude product of vinyl acetate containing impurities of the present invention is a mixture of vinyl acetate containing ethanol and can be obtained in large-scale industrial production.
[0050] In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. The test methods for which specific conditions are not specified in the following examples are generally carried out under conventional conditions or under conditions recommended by the manufacturer. Unless otherwise specified, all percentages and parts are by weight. The term "about" as used herein refers to a quantity, level, value, dimension, size or amount that differs by up to 30%, 20% or 10% compared to the quantity, level, value, dimension, size or amount of a reference product.
[0051] Throughout the specification and claims, unless otherwise required, the following words "comprise" and variations "comprising" and "including" will be understood to imply the inclusion of a stated integer or step, or a group of integers or steps, but not the exclusion of any other integer or step, or other group of integers or steps.
[0052] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art. The experimental materials used in the following embodiments include:
[0053] Experimental Materials:
[0054]
[0055]
[0056] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0057] Test Example 1: GCMS Detection
[0058] Test sample: high purity, impurity-free vinyl acetate
[0059] Related information of experimental equipment for GCMS detection: Agilent gas chromatograph-mass spectrometer, specifications 7890B-7000D.
[0060] Detection experimental steps:
[0061] 1. Turn on the machine: The order is to turn on the helium cylinder, turn on the GC power, turn on the MS power, and then turn on the computer.
[0062] 2. Enter the system and check the system configuration: Double-click GCMS REAL TIME to enter the main menu window; click system configuration on the left to set the system configuration and exit after confirming it is correct.
[0063] 3. Start the vacuum pump: Click the vacuum control icon on the left, the vacuum system screen will appear, click Advanced, the complete display content will appear; when the Vent valve light is green, start the mechanical pump; click Auto startup to start vacuum control; after the startup is completed, evacuate for 30 minutes and then you can perform tuning.
[0064] 4. Tuning: Click the Tuning icon to enter the tuning sub-menu, click the Peak monitor view icon, select Water in Monitor, and set the Detector voltage to 0.7KV (minimum) for air.
[0065] 5. Edit the method file.
[0066] 6. Sample measurement.
[0067]
[0068] From the above table and Figure 3 It can be seen that RT is the retention time, that is, the elution time of vinyl acetate is 2.324. The end time minus the start time represents the width of the vinyl acetate peak, that is, the width of the vinyl acetate peak is 0.407. The peak height represents the signal value output by the detector when vinyl acetate elutes from the column at the maximum concentration. The peak area refers to the integral value of the vinyl acetate peak height and the vinyl acetate retention time.
[0069] Example 1: Adsorption of ethanol in vinyl acetate by Q[6] solid powder material
[0070] At room temperature and pressure, take a 20mL culture bottle, add 5mL of vinyl acetate containing ethanol (prepared in the laboratory with a weight ratio of 98.72wt% vinyl acetate content and 0.37wt% ethanol content), take 0.4g Q[6] solid powder material and place it in the culture bottle, seal it, and place it at 20℃ for 48 hours until the ethanol is completely absorbed, and then air-dry the obtained powder.
[0071] After the adsorption is completed, the remaining vinyl acetate in the culture bottle can be measured by gas chromatography to detect whether there is any ethanol residue in the vinyl acetate.
[0072] Test Example 2: GCMS Detection
[0073] Test sample: Powder obtained in Example 1
[0074] Related information of experimental equipment for GCMS detection: Agilent gas chromatograph-mass spectrometer, specifications 7890B-7000D.
[0075] Detection experimental steps:
[0076] 1. Turn on the machine: The order is to turn on the helium cylinder, turn on the GC power, turn on the MS power, and then turn on the computer.
[0077] 2. Enter the system and check the system configuration: Double-click GCMS REAL TIME to enter the main menu window; click system configuration on the left to set the system configuration and exit after confirming it is correct.
[0078] 3. Start the vacuum pump: Click the vacuum control icon on the left, the vacuum system screen will appear, click Advanced, the complete display content will appear; when the Vent valve light is green, start the mechanical pump; click Auto startup to start vacuum control; after the startup is completed, evacuate for 30 minutes and then you can perform tuning.
[0079] 4. Tuning: Click the Tuning icon to enter the tuning sub-menu, click the Peak monitor view icon, select Water in Monitor, and set the Detector voltage to 0.7KV (minimum) for air.
[0080] 5. Edit the method file.
[0081] 6. Sample measurement.
[0082] Integrated peak list
[0083] peak start RT Finish Peak height area Area percentage 1 1.506 1.583 1.628 17722287.21 62993687.3 100 2 1.635 1.667 1.724 5631192.14 17707693.08 28.11 3 1.731 1.776 1.814 488961.46 1402720.94 2.23 4 2.174 2.238 2.283 174080.12 483879.17 0.77 5 2.43 2.462 2.507 68925.67 151504.05 0.24 6 2.809 2.847 2.912 2548082.38 5587661.12 8.87
[0084] From the above table and Figure 4 It can be seen that peak 1 is related to the elution of ethanol, peak 5 is related to the elution of vinyl acetate, and the other peaks are unknown impurities.
[0085] Relative to Figure 3 The GCMS spectrum of vinyl acetate with ethanol as an impurity shows that the GCMS spectrum of Q[6] solid powder material after being placed in vinyl acetate containing ethanol as an impurity for a period of time has changed. A new peak appears at position 1.583, and the peak area of this peak is very large. Therefore, in this component test, ethanol is the main component. This shows that Q[6] solid powder material can absorb ethanol in vinyl acetate containing ethanol as an impurity.
[0086] Example 2: Regeneration of Q[6] solid powder material
[0087] 0.4 g of the Q[6] solid powder material subjected to supersaturated adsorption of ethanol in Example 1 was heated in a vacuum oven at 100° C. for 2 hours. The sample was designated as Q[6]-D and kept for later use.
[0088] Test Example 3: H NMR Detection
[0089] Test sample: Regenerated powder Q[6]-D obtained in Example 2
[0090] Instrument related information: JNM ESC400M nuclear magnetic resonance spectrometer, single-phase 220v 50Hz3Kw.
[0091] Experimental steps and main parameters:
[0092] 1. Double-click the DELTA icon on the computer desktop to enter the NMR spectrometer operating software system, connect the spectrometer and the magnet, and enter the user name Delta and password Delta to log in to the spectrometer control interface.
[0093] 2. Add a sample menu item in the Sample tab, create a sample name, select D2O as the deuterated reagent and put it into the corresponding sample slot code. After confirming that it is correct, create the determination (Job title) corresponding to the sample in the lower right corner of the Sample tab.
[0094] 3. Select Hydrogen Spectrum under Job title, set the number of scans to 32 times in the experimental parameter interface, and after confirmation, click Submit Job in the lower right corner.
[0095] 4. After the experiment is completed, the operator should lock the sample and stop rotating the NMR tube, click the button (Eject), take the NMR tube out of the magnet and place it on the automatic sampler, and finally process the data results of the sample.
[0096] Q[6]-D, 1 H NMR(400MHz,D2O,298K,ppm)δ16.00(d,12H),5.53(s,12H),16.00(d,12H)
[0097] Depend on Figure 5 It can be seen that the signal of the hydrogen atom corresponding to ethanol has disappeared in the 1H NMR spectrum, which indicates that the Q[6] solid powder material has completed desorption and regeneration, and the ethanol molecules have been completely released.
[0098] Examples 3, 5, 7, 9: Adsorption of ethanol in vinyl acetate by Q[n] solid powder material
[0099] The steps of Examples 3, 5, 7, and 9 are basically the same as those of Example 1, except for the value of n in Q[n], the amount used, and the temperature for selectively removing the impurity ethanol from the vinyl acetate, as shown in the following table:
[0100] Serial number Materials and dosage Ethanol removal temperature Adsorption efficiency of Q[n] for ethanol Example 1 Q[6]0.4g 20℃ 94.535% Example 3 Q[5]0.26g 30℃ 80.785% Example 5 Q[7]0.55g 40℃ 88.256% Example 7 Q[8]0.51g 50℃ 86.068% Example 9 Q[6]0.32g 35℃ 93.093%
[0101] Examples 4, 6, 8, 10: Regeneration of Q[n] solid powder material
[0102] Examples 4, 6, 8, and 10 correspond to Examples 3, 5, 7, and 9, respectively, and are substantially the same as the steps of Example 2, except for the value of n in Q[n] and the temperature of the vacuum oven, as shown in the following table:
[0103] Serial number Vacuum oven temperature Example 2 100℃(Q[6]) Example 4 110℃(Q[5]) Example 6 120℃(Q[7]) Example 8 115℃(Q[8]) Example 10 120℃(Q[6])
[0104] After testing, the experimental effects of Examples 3, 5, 7, and 9 are equivalent to those of Example 1, and the experimental effects of Examples 4, 6, 8, and 10 are equivalent to those of Example 2.
[0105] In summary, it can be seen that the use of the caged compound solid powder material provided by the present invention for selectively removing impurity ethanol, its application and method, the separation process is simple to operate and has low equipment requirements; the separation process does not require distillation operation, has low energy consumption, saves energy, and reduces the production cost of ethanol and vinyl acetate; the present invention uses Q[n] solid powder material, which further reduces the cost compared with the crystal material used in the prior art; at the same time, the powder can adsorb ethanol through multiple channels such as the cavity, port and outer wall of its molecules, and has a better adsorption efficiency than the crystal; the caged compound solid powder material used has high stability and can be recycled, and the separation effect will not be reduced.
[0106] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. The use of a caged compound for selectively removing ethanol, wherein the caged compound has the structural formula in: n is selected from any integer between 5 and 8.
2. The use according to claim 1, characterized in that The cage compound is a solid powder. When n=5, the outer diameter of the solid powder Q[5] is The cavity diameter is Port diameter is When n=6, the outer diameter of the solid powder Q[6] is The cavity diameter is Port diameter is When n=7, the outer diameter of the solid powder Q[7] is The cavity diameter is Port diameter is When n=8, the outer diameter of the solid powder Q[8] is The cavity diameter is Port diameter is 3. A method for removing ethanol impurities from vinyl acetate using the use as claimed in claim 1, characterized in that: The molar ratio of the solid powder material of the cage-like compound to the impurity ethanol in the vinyl acetate is (1-1.5):
1.
4. The method according to claim 3, characterized in that The solid powder of the caged compound is selected from at least one of Q[5] solid powder, Q[6] solid powder, Q[7] solid powder and Q[8] solid powder.
5. The method according to claim 3, characterized in that The vinyl acetate is a mixture of vinyl acetate containing ethanol.
6. The method according to claim 5, characterized in that The vinyl acetate mixture containing ethanol is a crude product of vinyl acetate containing impurities obtained in large-scale industrial production.
7. The method according to claim 3, characterized in that The temperature of the selective removal of ethanol as an impurity from vinyl acetate is ≤50°C.
8. The method according to claim 7, characterized in that The temperature for selectively removing the impurity ethanol from the vinyl acetate is 30-50°C.
9. The method according to claim 3, characterized in that After selectively adsorbing ethanol, the solid powder of the cage-like compound can be desorbed, regenerated and reused.
10. The method according to claim 9, characterized in that The desorption regeneration temperature is 100-120°C.
11. Use of the method according to any one of claims 3 to 10 in removing impurity ethanol in the industrial production of vinyl acetate.
Citation Information
Patent Citations
Vinyl acetate separation and purification method
CN115894237A